Retail Sales in the Condition of Covid-19 - Terezova, Silvia (Research Papers, 2021)
The Covid-19 pandemic has affected all economic sectors. The outbreak of the pandemic and the measures for preventing the spread of the virus have led to changes consumers lifestyle, their shopping habits and to reduce retail sales. Faced with uncertainty about the future retailers need to adapt their activities to these changes. The purpose of the research is to assess the impact of Covid-19 to  retail sales and consumers’ behavior changes during the period from January 2020 until June 2020. The negative impact of Covid-19 is assessed by comparing the pace of decline in retail sales in Bulgaria and EU. The research is using data published by NSI and Eurostat about the index of the volume of retail sales which measures changes of the net sales, adjusted for price changes (deflated), i.e. the change of the total amount of goods sold, based on data adjusted for calendar and seasonal effects. On the other hand the retail sales changes are indicating the changing consumer behavior. The results of the research are showing that the EU is reducing the effects of the negative impact of Covid-19 on the net retail sales faster than Bulgaria.
Keywords: Retail trade; Consumer behavior; COVID-19; Retail sales